A green ionic liquid-based vortex-forced MSPD method for the simultaneous determination of 5-HMF and iridoid glycosides from Fructus Corni by ultra-high performance liquid chromatography. (1st April 2018) - Du, Kunze; Li, Jin; Bai, Yun; An, Mingrui; Gao, Xiu-mei; Chang, Yan-xu
Highlights: Ionic liquid was used as a green elution reagent in vortex-forced MSPD process. IL-based vortex-forced MSPD method was used to detect iridoid glucosides and 5-HMF. The alternative method for determination of 5-HMF in food analysis. An efficient method for quality control of Fructus Corni. Abstract: A simple and green ionic liquid-based vortex-forced matrix solid phase dispersion (IL-VFMSPD) method was presented to simultaneously extract 5-hydroxymethyl furfurol (5-HMF) and iridoid glycosides in Fructus Corni by ultra-high performance liquid chromatography. Ionic liquid was used as a green elution reagent in vortex-forced MSPD process. A few parameters such as the type of ionic liquid, the type of sorbent, ratio of sample to sorbent, the concentration and volume of ionic liquid, grinding time and vortex time, were investigated in detail and an orthogonal design experiment was introduced to confirm the best conditions in this procedure. With the final optimized method, the recoveries of the target compounds in Fructus Corni were in the range of 95.2–103% (RSD < 5.0%) and the method displayed a good linearity within the range of 0.8–200 μg mL −1 for morroniside, sweroside, loganin, cornuside and 1.2–300 μg mL −1 for 5-HMF. The limits of detection ranged from 0.02 to 0.08 μg mL −1 for all compounds. The results showed that the newly established method was efficiently applied to extract and determine iridoid glycosides and 5-HMF for quality control of Fructus Corni .